Effectiveness of Ameliorant Humic Acid and Silica Based on Availability of Sandy Soil Nitrogen for Rice - Siswanto; Wanti Mindari; Setyo Budi Santoso; Rusyla Dwi Rahayu (Nusantara Science and Technology Proceedings, 2021)
Sandy soils generally have high macro pores and a low ability to provide water and plant nutrients. This condition is caused by the soil matrix which has almost no negative charge, so there is no strong adsorption capacity for ions and water. The next impact is that nutrients and water are easily lost because they are washed or evaporated. Nitrogen loss has been reported to reduce rice production by 6.10%. The purpose of the study was to examine the effectiveness of ameliorants based on humic acid and silica in improving nutrient availability and sandy soil water. Humic acid from compost and silica from husk charcoal is expected to increase the negative charge of the soil (cation exchange capacity) so that it can adsorb and fix (chelate) nutrient ions such as nitrogen. The study was structured using a factorial Completely Randomized Design (CRD). The first factor is silica dose with a level of 0 ton/ha, 0.5 ton/ha, 1 ton/ha, and 1.5 ton/ha. The second factor is the dose of humic acid with a level of 0 kg/ha, 20 kg/ha, 40 kg/ha, and 60 kg/ha. Rice plants are used as growth indicators. Observation parameters include the availability of N in the soil, the growth of rice plants which includes plant length and the number of tillers, and plant chlorophyll. The results showed that the combination of humic acid and silica had no significant effect on plant length, the number of tillers, and nitrogen availability in the soil. However, it has a significant effect on plant chlorophyll.